Developing Flashcard Media to Teach Speaking Skill at MTs Maftahul Ulum Jatinom Blitar - Hidayah, Fitria Hidayah; Rofi'ah, Siti; Mubarok, Tyas Alhim; Makrifah, Istina Atul (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This study aims to develop an instructional medium in the form of flashcards to enhance students’ speaking skills in English language learning. The research subject was 26 students of 7th grade at MTS Maftahul Uluum Jatinom Blitar. The development procedure referred to ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The background of this study stems from students' difficulties in speaking English and the lack of interest in learning. To address this issue, the researcher designed flashcard with the interesting and colorful pictures.The developed product underwent validation by a media expert and a material expert, and was subsequently tested through student trials. The material validation score was 88%, the media validation score was 98%, and the student satisfaction score was 90%, all of which indicate that the media is highly feasible. The result of student satisfaction analysis indicates that flashcard is effective to increase student interest. Based on the findings, this learning tool is deemed both effective and practical in enhancing students’ interest and may serve as an alternative instructional resource in English language teaching.